(untitled) (Medical Forum Monthly, 2021)
Objective: Objective of the study is to determine the prevalence of preoperative Pulmonary Artery Hypertension (PAH) and its severity in patients undergoing Mitral Valve surgery at a tertiary care hospital in Karachi, Pakistan. Study Design: Descriptive Observational study Place and Duration of Study: This study was conducted at the Cardiac Surgery Department of National Institute of Cardiovascular Diseases (NICVD) Karachi for a period of six months December 2020 to May 2021. Materials and Methods: Non-probability, Consecutive Sampling. Patients fulfilling the inclusion criteria were included in this study, Patients diagnosed with Mitral Regurgitation (MR) or Moderate to Severe Mitral Stenosis (MS) undergoing mitral valve surgery. Pulmonary Artery Hypertension was labelled PAH [+] if preoperative systolic pulmonary artery pressure (sPAP) ≥ 40 mmHg, as measured with Doppler echocardiography, otherwise it was labelled as PH [-]. Data was entered and analysis using SPSS version-21. Variables was expressed using appropriate descriptive statistics such as mean ± SD, median (IQR), maximum and minimum. Frequency and percentages were calculated for categorical variables. Results: During this period of study 68 patients were included in study who were operated for Mitral Valve Replacement(MVR). It included 50(74%) females and 18 males (26%).In these patients only 1(1.4%) was operated through minimally invasive mitral valve replacement whereas 67(98.52%) patients with conventional mitral valve replacement (MVR) through median sternotomy. All the patients who were operated had severe disease. Pulmonary Artery hypertension (PAH) was present in 23(74.2%) out of 33 Mitral Regurgitation (MR) patients. Pulmonary Artery hypertension (PAH) was present in 23(74.2%) out of 31 patients who had Mitral Stenosis MS. Overall In-hospital mortality in our study was 10.3% (7 out of 68 patients). Conclusion: Prevalence of PAH is high in patients undergoing Mitral Valve Replacement surgery. Major factors associated with post-operative mortality include prolonged ICU stay, prolonged ventilation and need for high inotropic support.